2021
DOI: 10.1371/journal.pone.0259107
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for surgical site infection in patients undergoing colorectal surgery: A meta-analysis of observational studies

Abstract: Objective Surgical site infection (SSI) is the second most prevalent hospital-based infection and affects the surgical therapeutic outcomes. However, the factors of SSI are not uniform. The main purpose of this study was to understand the risk factors for the different types of SSI in patients undergoing colorectal surgery (CRS). Methods PubMed, EMBASE, and Cochrane Library databases were searched using the relevant search terms. The data extraction was independently performed by two investigators using a st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(35 citation statements)
references
References 69 publications
(128 reference statements)
4
22
0
Order By: Relevance
“…It has been reported that cigarette smoking can delay wound healing, which may lead to a risk of SSI. Our study found that patients who smoked had a higher risk of SSI in comparison with patients who did not smoke, which was consistent with the conclusions of the National Nosocomial Infections Surveillance System (NNIS) guidelines ( 35 , 36 ).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…It has been reported that cigarette smoking can delay wound healing, which may lead to a risk of SSI. Our study found that patients who smoked had a higher risk of SSI in comparison with patients who did not smoke, which was consistent with the conclusions of the National Nosocomial Infections Surveillance System (NNIS) guidelines ( 35 , 36 ).…”
Section: Discussionsupporting
confidence: 90%
“…Clinical study ( 36 ) has confirmed that surgical duration is a risk factor for SSI. The reasons for this are as follows: (I) the exposure of the surgical incision to air for a long time increases the chance of pathogen pollution; (II) the longer the operation time, the more complex the operation and the greater the trauma; and (III) prolonged anesthesia decreases immunity.…”
Section: Discussionmentioning
confidence: 88%
“…The hospital facility was included as a random intercept to account for within-hospital clustering. The following SSI risk factors were included in the model: surgical category [ 5 ]; type of admission (elective or non-elective) [ 13 ]; CCI score [ 14 ]; blood transfusion [ 15 ]; alcohol, drug, and/or nicotine use [ 10 , 16 ]; and comorbidities including chronic obstructive pulmonary disease (COPD) [ 17 , 18 ]; peripheral vascular disease [ 19 , 20 ]; congestive heart failure [ 19 ]; rheumatic disease [ 20 ]; hypertension [ 19 ]; obesity [ 10 , 16 , 20 ]; and blood disorders [ 19 ].…”
Section: Methodsmentioning
confidence: 99%
“…Quality was assessed using the NOS, and involved the selection of the study groups, evaluation of intercomparability between the groups, and measurement of outcomes, with a maximum score of 9 points; studies with ≥6 points were considered to be of relatively higher quality. 9 …”
Section: Methodsmentioning
confidence: 99%